2021
DOI: 10.1021/acs.inorgchem.1c02115
|View full text |Cite
|
Sign up to set email alerts
|

Azide–Alkyne “Click” Reaction in Water Using Parts-Per-Million Amine-Functionalized Azoaromatic Cu(I) Complex as Catalyst: Effect of the Amine Side Arm

Abstract: A series of Cu(II) complexes, 1−4 and 6, were synthesized through a reaction of amine-functionalized pincer-like ligands, HL 1,2 , L a,b , and a bidentate ligand L 1 with CuCl 2 •2H 2 O. The chemical reduction of complex 1 using 1 equiv of sodium Lascorbate resulted in a dimeric Cu(I) complex 5 in excellent yield. All of the complexes, 1−6, were thoroughly characterized using various physicochemical characterization techniques, single-crystal X-ray structure determination, and density functional theory calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 115 publications
0
8
0
Order By: Relevance
“…In this reaction, Cu(I) served as an active species, capable of generating from Cu(II) by applying a reducing agent such as sodium ascorbate. [30] The Cu(II) moiety can also be reduced without using a reducing agent, either by alkyne homocoupling or solvent oxidation. [31] However, the use of in-situ generated organic azides in the Click reaction is a good choice and reduces the detonation nature of organic azides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this reaction, Cu(I) served as an active species, capable of generating from Cu(II) by applying a reducing agent such as sodium ascorbate. [30] The Cu(II) moiety can also be reduced without using a reducing agent, either by alkyne homocoupling or solvent oxidation. [31] However, the use of in-situ generated organic azides in the Click reaction is a good choice and reduces the detonation nature of organic azides.…”
Section: Introductionmentioning
confidence: 99%
“…Recent Nobel Prizes in Click Chemistry have triggered this field in the science domain. In this reaction, Cu(I) served as an active species, capable of generating from Cu(II) by applying a reducing agent such as sodium ascorbate [30] . The Cu(II) moiety can also be reduced without using a reducing agent, either by alkyne homocoupling or solvent oxidation [31] .…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of redox non-innocent behavior of the azo-aromatic compound, we designed and synthesized the pincer-like azo-aromatic ligands ( L 1 – 3 , Scheme ) as well as their cobalt­(II) complexes ( 1 – 3 ) (Scheme ). Azo aromatics are known to exist in one-electron reduced azo-anion radicals and two-electron reduced hydrazido forms. ,,, It is also reported that the azo moiety of the ligand can abstract a hydrogen atom efficiently from coordinated deprotonated alcohol, leading to dehydrogenative formation of carbonyl compounds. Complexes 1–3 have shown facile L/L • and Co­(II)/Co­(I) reductions in a close-lying redox potential, which might be beneficial for chemical transformations that occur through two electron oxidations.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal complexes supported by pincer ligands have been used as catalysts in azide‐alkyne Click reactions [12] . Samanta and co‐workers synthesized a series of pincer type of copper(II) complexes having new strong π‐acceptor type azo‐aromatic ligands and utilized as catalysts for azide‐alkyne cycloaddition reactions [11c] . Our group reported a series of copper(II) complexes supported by arylselenolate‐based ligands for azide‐alkyne cycloaddition in water [13] .…”
Section: Introductionmentioning
confidence: 99%